Nodulation and Nitrogen fixation in rice : (International Rice Research Institute, 1992)
The book gathers all papers presented at International Workshop to Assess the Potential for Nodulation and Nitrogen Fixation in Rice was held at IRRI. The papers assess knowledge and recommend research strategies for the future